Heterogeneity of Organization of Subcompartments in DSB Repair Foci - Abate, Natnael G.; Hendzel, Michael J. (Frontiers in Genetics, 2022)
Cells assemble compartments around DNA double-strand breaks (DSBs). The assembly of this compartment is dependent on the phosphorylation of histone H2AX, the binding of MDC1 to phosphorylated H2AX, and the assembly of downstream signaling and repair components. The decision on whether to use homologous recombination or nonhomologous end-joining repair depends on competition between 53BP1 and BRCA1. A major point of control appears to be DNA replication and associated changes in the epigenetic state. This includes dilution of histone H4 dimethylation and an increase in acetylation of lysine residues on H2A and H4 that impair 53BP1 binding. In this article, we examined more closely the spatial relationship between 53BP1 and BRCA1 within the cell cycle. We find that 53BP1 can associate with early S-phase replicated chromatin and that the relative concentration of BRCA1 in DSB-associated compartments correlates with increased BRCA1 nuclear abundance as cells progress into and through S phase. In most cases during S phase, both BRCA1 and 53BP1 are recruited to these compartments. This occurs for both IR-induced DSBs and breaks targeted to an integrated LacO array through a LacI-Fok1-mCherry fusion protein. Having established that the array system replicates this heterogeneity, we further examined the spatial relationship between DNA repair components. This enabled us to precisely locate the DNA containing the break and map other proteins relative to that DNA. We find evidence for at least three subcompartments. The damaged DNA, single-stranded DNA generated from end resection of the array, and nuclease CtIP all localized to the center of the compartment. BRCA1 and 53BP1 largely occupied discrete regions of the focus. One of BRCA1 or 53BP1 overlaps with the array, while the other is more peripherally located. The array-overlapping protein occupied a larger volume than the array, CtIP, or single-stranded DNA (ssDNA). Rad51 often occupied a much larger volume than the array itself and was sometimes observed to be depleted in the array volume where the ssDNA exclusively localizes. These results highlight the complexity of molecular compartmentalization within DSB repair compartments.